Effectiveness Of Health Education On Knowledge Of The Peopleabout General Complication And Preventive Policies Of Dengue Fever - Miss. Pooja Chavan, Mrs. Sangeeta Patil, Anagha Katti, Sheetal Kadam, Ajit Anandrao Pawar, Miss. Shubhangi Chaudhari, Mr. Rajdeep Desai (International Journal of Advanced Science and Technology, 2020)
Background of the study:-Dengue is one of the most common mosquitos borne viral disease in India. Health education is best method to create an awareness to prevent complication. Objective:-Study investigated the effectiveness of health education on knowledge of the people about general complication and preventive policies of dengue fever. Material and methods: -The experimental study was done onknowledge of the people about general complication and preventive policies of dengue fever in Koyanavasahat, Malkapur. Total sample size 40.convinient sample technique was used.pre test done with self-prepared questionnaire. Samples selected as per inclusion criteria. One group pre-test post-test design was used. After 7 days post-test taken with help of same questionnaire. Poster exhibition done as a health education onon complication and preventive policies of dengue fever. Data was analysed. Sample consisted 40people selected by convenient sampling technique with one group pre and post-test design. Pre-test taken with help of self-prepared questionnaire and health education with help of poster exhibition given on complication and preventive policies of dengue fever. Post-test taken after one week with help of self-prepared structured questionnaire which was validated by experts.The data was analysed using descriptive and inferential statistics. Samples included according to inclusion criteris and those know Marathi. Results: -Result of the present study shows that pre-test score 7.775 and, in the post-test, score 12.4 and t = 19.410, P=0.0001. It proves that there was statistically significantdifference in pre and post-test on knowledge score. The health education shows significant improvement in the knowledge of peoples in selected area of Koyanavasahat, Malkapur regarding the Preventive Policy and Complication of dengue fever. Conclusion: - This study shows the knowledge of the people increased after health education with help of poster exhibition on complication and preventive policies of dengue fever in Koyanavasahat, Malkapur.